2013
DOI: 10.1371/journal.pone.0078713
|View full text |Cite
|
Sign up to set email alerts
|

miR-192 Directly Binds and Regulates Dicer1 Expression in Neuroblastoma

Abstract: Neuroblastoma (NB) arises from the embryonic neural crest and is the most common extracranial solid tumor in children under 5 years of age. Reduced expression of Dicer1 has recently been shown to be in correlation with poor prognosis in NB patients. This study aimed to investigate the mechanisms that could lead to the down-regulation of Dicer1 in neuroblastoma. We used computational prediction to identify potential miRs down-regulating Dicer1 in neuroblastoma. One of the miRs that were predicted to target Dice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…It has been reported that miR-192 was downregulated in colon cancer, osteosarcoma, and bladder cancer [9][10][11]. However, upregulation of miR-192 was found in pancreatic ductal adenocarcinoma, neuroblastoma, and gastric cancer [12][13][14]. It indicted that the abnormal expression of miR-192 has tissue specificity in human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that miR-192 was downregulated in colon cancer, osteosarcoma, and bladder cancer [9][10][11]. However, upregulation of miR-192 was found in pancreatic ductal adenocarcinoma, neuroblastoma, and gastric cancer [12][13][14]. It indicted that the abnormal expression of miR-192 has tissue specificity in human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…More, recently, miRs have been reported to affect the development of depression and have been used as an antidepressant treatment approach (13,14), in connection with their regulation of the development and function of the nervous system (15,16). Notably, miR-192 has been shown to play an important role in neuroblastoma, a malignancy that shares a close correlation with depression (17,18). miR-192, -197, and -346 have been found to be highly expressed in follicular thyroid carcinoma, and EGF containing Fibulin (Fbln) extracellular matrix protein-2 (Fbln-4) is suppressed by overexpressed miR-346, indicating that miR-192 may be associated with Fbln-4 (19).…”
mentioning
confidence: 99%
“…The MIR192 gene is transcribed together with miR-194 [7]. Several studies reported the upregulation of miR-192 in different cancer types, including gastric cancer, hepatocellular carcinoma, and neuroblastoma [8][9][10]. Conversely, miR-192 was downregulated in colorectal cancer and hematological disorders, as well as in lymphoblastic leukemia (ALL) where it was associated with poor prognosis (Supplemental Table 1) [11,12].…”
Section: Introductionmentioning
confidence: 99%